2022
DOI: 10.1038/s41598-022-22060-z
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 quasi-species analysis from patients with persistent nasopharyngeal shedding

Abstract: At the time of a new and unprecedented viral pandemic, many questions are being asked about the genomic evolution of SARS-CoV-2 and the emergence of different variants, leading to therapeutic and immune evasion and survival of this genetically highly labile RNA virus. The nasopharyngeal persistence of infectious virus beyond 17 days proves its constant interaction with the human immune system and increases the intra-individual mutational possibilities. We performed a prospective high-throughput sequencing stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…In contrast, other studies found a similar RNA viral load for Omicron-infected and Delta-infected patients [ 42 , 43 ]. These results suggest that the observed higher transmissibility of Omicron BA.1 is unrelated to an increased shedding of infectious viral particles, in agreement to our own results [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, other studies found a similar RNA viral load for Omicron-infected and Delta-infected patients [ 42 , 43 ]. These results suggest that the observed higher transmissibility of Omicron BA.1 is unrelated to an increased shedding of infectious viral particles, in agreement to our own results [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…This can be attributed to the relatively low mutation rate of the virus, which, combined with the short time interval between samples, did not allow enough time for mutations to occur and become fixed within the context of global transmission in an immunocompetent population [ 35 ]. In contrast, other studies performing quasi-species analysis, even before the emergence of VOCs, have shown high intra-patient variability in severe and immunosuppressed patients with persistent or prolonged viral shedding [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that reported intrahost SARS-CoV-2 genetic diversity have notably provided data for immunocompromised, chronically infected patients, patients treated with monoclonal antibodies targeting viral spike, and different body compartments from the same patients (Supporting Information: Table S1). Choi et al 112 They reported that intrahost diversity was higher in the persistent than nonpersistent patients, with minority N501Y and P681H mutations in the patients of both groups. Caccuri et al described the case of a 59year-old male patient who was immunocompromised due to follicular lymphoma and chronically infected with SARS-CoV-2 for 222 days.…”
Section: Quasispecies For Sars-cov-2mentioning
confidence: 98%
“…The cancer patients exhibited significantly higher intrahost viral genetic diversity than the healthcare workers. Dudouet et al performed next‐generation sequencing with Nanopore technology of SARS‐CoV‐2 genomes from 78 patients with nasopharyngeal virus persistence beyond 17 days and from 47 patients without such virus persistence 112 . They reported that intrahost diversity was higher in the persistent than nonpersistent patients, with minority N501Y and P681H mutations in the patients of both groups.…”
Section: The Case For Covid‐19 Including Sars‐cov‐2mentioning
confidence: 99%
“…Two scenarios are possible from the data observed on this study. One scenario could be the intra-individual emergence of viral quasi-species that fluctuates in frequency over time [ 20 , 21 , 22 ]. A second scenario could be the introduction of new viral quasi-species by a second and independent infection event which could explain the burst of mutations from day 1 to day 37.…”
Section: Case Presentationmentioning
confidence: 99%